Flow With Nature Treatment for Depression: Participants’ Experiences - Salonen, Kirsi; Hyvönen, Katriina; Paakkolanvaara, Jane-Veera; Korpela, Kalevi (Frontiers in Psychology, 2022)
This study examined Flow with Nature (FWN) treatment, which is an integrative intervention (rehabilitation) based on eco and environmental psychology, psychotherapeutic theories, and professional psychological practice. FWN is intended for depression rehabilitation with the help of social support, nature environments and FWN exercises. Exercises encourage sensing the environment, mindful awareness, psychological processing, and focusing on the future. The FWN treatment proceeds in separate stages (horizon, growth, path), which emphasise nature, group (social support), and FWN exercises differently. This study focused on the experiences of the participants in the FWN treatment. Finnish adults who had been diagnosed with clinical depression took part in the FWN treatment (N = 82) and answered feedback questions (by paper, electronic questionnaire, or phone discussion). Answers were analysed using theory-based content analysis. Data were collected between spring 2019 and spring 2020. The majority of the participants were women (82%) and on average 44 years old. Content analysis revealed that the participant feedback answers were in agreement with the central theoretical themes of FWN. The participants emphasised the significance of nature, social support and exercises differently. Moreover, the significance of these ingredients differed according to the stages of treatment: in the horizon stage restorative (e.g., fascination) and comprehensive nature experiences (e.g., connectedness with nature), in the growth stage social support (e.g., peer support), and in the path stage environmental self-regulation (e.g., nature as a part of life) were emphasised. These results are in accordance with the objectives of the stages and seem to support the phase-based rationale. The participants’ experiences of the key elements of the intervention, social support and nature environment were experienced mainly positively, which supports their inclusion in future intervention versions. In the future, FWN exercises should be developed to better enable participants’ possibilities for concentration and being present in the moment (mindfulness). Exercises should also be simplified to match the target group’s cognitive abilities.